THE ROLE OF DIGITAL LEADERSHIP IN ACHIEVING ORGANIZATIONAL EXCELLENCE AN APPLIED STUDY AT THE UNIVERSITY OF TIKRIT (World Economics and Finance Bulletin, 2022)
The main objective of the research was to study the role of digital leadership in achieving institutional excellence by applying to the University of Tikrit. The descriptive analytical method was relied on in describing and analyzing the opinions of the respondents about the research variables. The study population is represented by the employees of Tikrit University, its faculties and departments. Where a random sample of (82) individuals working in electronic administration at the university in question was selected. The most important results that have been reached are the approval of the respondents' opinions about the dimensions of digital leadership and organizational excellence. The results of the research also proved the validity of the research hypotheses, which states that there is a significant impact of digital leadership in achieving institutional excellence. And organizations that are keen to adopt the digital leadership style enjoy a high level of organizational excellence
Keywords: digital leadership; innovation; knowledge; organizational excellence